Gentian stem harvesting device based on bionic flexible rollers - Cui, Hongguang; Zhang, Jinming; Chen, Guangshuo; Tang, Qingchen; Huang, Wenzhong; Wu, Liyan (International Journal of Agricultural and Biological Engineering, 2024)
Aiming at the problem of incomplete stem removal in the process of Gentian root and stem separation, a roller-type Gentian stem removal device was designed. Based on the mechanical characteristics of Gentian stems and the force analysis of the extraction process, the operating conditions for the complete removal of Gentian stems were determined. When the tensile force exerted by the stem-pulling rollers on the Gentian stems is less than the tensile force of the Gentian stems and greater than the maximum tensile force required for the Gentian stems to be removed at the stem bases, the complete removal of Gentian stems from the stem base can be realized. The bionic design method is used to construct the bionic flexible surfaces tructure of the stem-pulling rollers by taking the tree frog toe pad as the bionic prototype and investigating its flexible surface microstructure and friction-enhancing characteristics. EDEM simulation software is used to establish the contact model between the bionic flexible stem-pulling rollers and Gentian stems, and the optimal structural parameters of the bionic flexible surface are determined through simulation tests. The optimal working parameters of the bionic flexible roller are determined through test rig tests. The experimental results showed that when the diameter of the hexagonal prism of the bionic surface was 5.67 mm, the spacing of adjacent hexagonal prisms was 2.62 mm, and the height of the hexagonal prism was 3.21 mm, the bionic flexible stem-pulling rollers exerted a maximum tensile force of 30.23 N, and the Gentian stems were not broken. When the speed of the rollers was 195 r/min, the spacing between stem-pulling rollers was 3.0 mm, and the height of the rollers clamping position was 250 mm, the maximum tensile force required for Gentian stem removal was 13.88 N, and the netremoval rate reached 94.35%. Keywords: Gentian harvest, bionic design, increased friction, bionic flexible rollers DOI: 10.25165/j.ijabe.20241706.8453 Citation: Cui H G, Zhang J M, Chen G S, Tang Q C, Huang W Z, Wu L Y. Gentian stem harvesting device based on bionic flexible rollers. Int J Agric & Biol Eng, 2024; 17(6): 66–75.